Parental Involvement in the Holistic Development of Learners with Special Needs - Ynion, Fretzie Gay; Layona, Shirley (International Journal of Sustainability and Advanced Integrated Research, 2026)
This study determined teachers’ perceptions of parental involvement in the holistic development of learners with special needs in selected schools in Aranyaprathet, Sakaeo, Thailand during School Year 2025–2026. Anchored on Bronfenbrenner’s Ecological Systems Theory, Epstein’s Framework of Overlapping Spheres of Influence, Hoover-Dempsey and Sandler’s Model of Parental Involvement, and Bandura’s Social Learning Theory, the study used a quantitative descriptive-survey and descriptive-correlational design. Data were gathered from 75 Filipino teachers handling learners with special needs through a validated structured questionnaire and were analyzed using frequency counts, percentages, means, and Pearson r. Findings showed that most respondents were female, in early adulthood, had five years or less of teaching experience, taught in the primary grades, and worked in public schools. Parents were perceived as very highly involved in learners’ academic, social, emotional, physical, behavioral, and functional and life skills development, while learners demonstrated a high level of holistic development across cognitive, emotional, social, and physical/motor domains. However, Pearson correlation results showed no significant relationship between parental involvement and learners’ holistic development. Teachers also reported very serious challenges, particularly ineffective communication, limited parental knowledge of special education practices, limited time, and dependence on teachers. The study recommends stronger home–school partnerships and evidence-based parent training to support learners with special needs. The study supports SDG 4, SDG 3, SDG 10, and SDG 17 by promoting inclusive education, learner well-being, reduced educational barriers, and school–family collaboration. Its sustainability impact lies in strengthening educational, institutional, community, and well-being support systems for learners with special needs.